Application of natural seaweed modified mortar for sustainable concrete production - Siddique, Md. Nurul Islam; Zularisam, A. W. (IOP Publishing Ltd, 2018)
The effect of seaweed such as Eucheuma Cottonii (gel) and Gracilaria Sp. modified mortar on the properties of sustainable concrete was investigated. Pre-experiment and main-experiment was conducted to carry out this study. Pre-experiment was conducted to study the compressive strength of the sustainable concrete. The main-experiment studied the compressive and splitting strength. Results showed that seaweed modified mortar yielded satisfactory compressive and splitting strength of 30 MPa and 5 MPa at 28 days.